The MALAT1 gene polymorphism and its relationship with the onset of congenital heart disease in Chinese. Issue 3 (22nd May 2018) - Li, Qian; Zhu, Wenying; Zhang, Bei; Wu, Yiping; Yan, Sen; Yuan, Yufeng; Zhang, Haiyan; Li, Jie; Sun, Kai; Wang, Hua; Yu, Tingting
Abstract : Many long non-coding RNAs (lncRNAs), including lncRNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), are involved in various cardiac diseases. We evaluated the effects of tag single nucleotide polymorphisms (tag-SNPs) on MALAT1 gene in a Chinese population of children with congenital heart disease (CHD). In the present study, 713 CHD patients and 730 gender- and age-matched children without CHD were genotyped for MALAT1 tag-SNPs rs11227209, rs619586, and rs3200401. Further investigation of SNP's function was performed by luciferase assay. Statistical analyses, including uni- and multivariate logistic regression were performed to quantitate the association between these tag SNPs and CHD. We discovered that MALAT1 rs619586 GG allele was significantly associated with lower risk of CHD (odds ratio (OR) = 0.77, 95% confidence interval (CI) = 0.59–0.92, P =0.014) in additive model. Functional investigation indicated that G allele of rs619586 could trigger higher expression of MALAT1. We demonstrated that the functional MALAT1 polymorphism rs619586 A>G was significantly associated with CHD susceptibility in Chinese population, potentially via regulating MALAT1 expression.